Impact of initial rhythm control with cryoballoon ablation versus drug therapy on atrial fibrillation recurrence and quality of life: results from the Cryo-FIRST study. (24th May 2021) - Pavlovic, N; Kuniss, M; Velagic, V; Hermida, JS; Healey, S; Arena, G; Badenco, N; Meyer, C; Chen, J; Iacopino, S; Anselme, F; Kaplon, RE; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Medtronic OnBehalf: The Cryo-FIRST Investigators Background: Cryoballoon ablation (CBA) as a first-line rhythm control strategy is superior to antiarrhythmic drugs (AADs) for preventing atrial arrhythmia recurrence; however, the impact of first-line CBA specifically on atrial fibrillation (AF) recurrence and quality of life (QoL) has not been well characterized. Purpose: To compare AF recurrence and QoL following first-line CBA vs. AAD therapy in patients with paroxysmal AF within the CryoFIRST trial (NCT01803438). Methods: Patients with recurrent symptomatic paroxysmal AF who had not been administered class I or III AAD therapy for >48 hours were enrolled at 18 sites in 9 countries. Patients were randomized (1:1) to CBA or AAD treatment (Class I or III). Subjects were followed by 7-day Holter at 1, 3, 6, 9, and 12 months. Time-to-first AF recurrence outside of a 90-day blanking period was estimated by Kaplan-Meier analysis. QoL was evaluated using the Atrial Fibrillation Effect on Quality of Life (AFEQT) and 36-Item Short Form Health Survey (SF-36) v2 questionnaires. Results: Of the 218 randomized subjects, 187 (86%) completed the 12-month follow-up. By intention-to-treat (ITT) analysis, freedom from AF after blanking was achieved in 86.6% in the CBA and 74.5% in the AAD group (p = 0.023). There was no difference in the time-to-first serious adverse event between groups. In total, 84.3% of patients in the CBA vs. 75.0% of patients in the AAD arm had a clinically important improvement (≥5 points) in the AFEQT summary score. The adjusted mean difference in the AFEQT summary score at 12 months was 9.9 points higher in the CBA group (95% CI: 5.5-14.2; P < 0.001). All AFEQT subscale scores were more favorable in the CBA vs. AAD group at 12 months. There were no significant group differences in any of the SF-36 health domain scores at 12 months in the ITT analysis. In the per-protocol analysis, clinically important and significant group differences in favor of CBA were observed at 12 months for 3 of 8 SF-36 health domain scores (physical functioning, general health and social functioning). Conclusion: CBA is superior to AAD for preventing AF recurrence and improving AF-specific QoL in patients with paroxysmal AF.